Beetle & the Hollowbones - Layne, Aliza; Reiss, Natalie; Acampora, Kristen (New York : Atheneum Books for Young Readers, 2020)
Twelve-year-old goblin and witch-in-training Beetle enlists her former best friend, Kat Hollowbones, to help stop Kat's sorceress aunt from demolishing the mall where Beetle's friend Blob Ghost is trapped.
Keywords: Witches -- Comic books, strips, etc; Goblins -- Comic books, strips, etc; Ghosts -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Witches -- Fiction; Goblins -- Fiction; Ghosts -- Fiction; Magic -- Fiction; Cartoons and comics; Comics (Graphic works)